CURRENT ENVIRONMENTAL AND HYGIENIC PROBLEMS AND THE MAIN RISK FACTORS FOR WORKING CONDITIONS IN CARPET PRODUCTION - Zhumaeva, A.A. (Journal of Medical Genetics and Clinical Biology, 2024)
The aim of this present work became the ecology-hygienic characteristic of carpet manufacture by the example of “Vitebsk carpets” and development of recommendations on optimization of working conditions. decrease of case rate and maintenance of medicine-technological safety. In work the basics are considered professional the harm. Working on an organism of workers. It is established. that the dust allocated in air exceeds maximum concentration limit in 1.7-18.5 times at various stages of technological process of carpet manufacture.